(3GdahGcg GdLfjI Ydi TQM GdCLQhejI dNGdO GdCRgQjs - (3GdbdjhHj GdCRgQj, CHh GdYHGS, TgGH GdOjf, CMeO Hf CMeO Hf SdGeI, (B1069 (3g`s ((3CHh HcQ Hf eMeO CHG GdWGgQ cGedjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY ebGe ef fUH faSg dfaY GdYHGO hHYO agPG eG JjSQ LeYg ef GdahGFO Ydi TQM GdCLQhejI dehdGfG GdTjN NGdOs
(3BNQgG (B:s
(3Ch hGSWI Hjf GdeMVI hZjQgG hgj ef EVGaI GdTjA Edi faSg Ch ef EVGaI GdeSei Edi GdGSe Ch EVGaI eG Hjfg hHjf eVGag Yehe ef hLg CbhGd KdGKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 92s
(3eYLe GdeDdajf(B: 1 / 94s
(3cTa GdXfhf(B: 2 / 1797s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs